2004
DOI: 10.1542/peds.2004-0583
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Lysosomal Storage Disorders: Clinical Evaluation of a Two-Tier Strategy

Abstract: Newborn screening for selected LSDs is possible with current technology. However, additional development is required to provide a broad coverage of disorders in a single, viable program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 28 publications
2
59
0
5
Order By: Relevance
“…Methods for high throughput screening of GAA activity, using the newborn screening dried blood filter specimen (DBS), have been developed and are being validated in large population screening programs 2931,107. If successful, newborn screening for Pompe disease can become a reality.…”
Section: Genetic Counseling Prenatal Diagnosis and Screeningmentioning
confidence: 99%
“…Methods for high throughput screening of GAA activity, using the newborn screening dried blood filter specimen (DBS), have been developed and are being validated in large population screening programs 2931,107. If successful, newborn screening for Pompe disease can become a reality.…”
Section: Genetic Counseling Prenatal Diagnosis and Screeningmentioning
confidence: 99%
“…Early diagnosis will thus be essential and can only be achieved by increasing awareness for MPS III and, probably best, by NBS. Earlier studies showed that NBS for MPS IIIA is feasible, for example, by measuring HS concentrations or lysosomal protein concentrations in dried blood spots 22, 31, 32. Early diagnosis, especially through NBS, will make reliable assessment of the phenotype crucial, either by genotyping or, if that is inconclusive, by other methods such as the method reported here.…”
Section: Discussionmentioning
confidence: 87%
“…The diagnosis may be confi rmed by assay of enzyme levels in tissue samples and gene sequencing. Prenatal diagnosis is possible 7 .…”
Section: The Casementioning
confidence: 99%
“…Treatment remains largely supportive 7 . The behavioral disturbances of MPS-III respond poorly to medication.…”
Section: The Casementioning
confidence: 99%